SISTEM BAGI HASIL PADA PENGELOLAAN BISNIS SOCCER ANTARA OWNER DENGAN PENGELOLANYA DI FOURGEE MINI SOCCER & BEZZIE MINI SOCCER MENURUT AKAD MUDHARABAH - Fajar Ramadhansyah; Dedy Sumardi; Husni bin Abdul Jalil (Al-Mudharabah: Jurnal Ekonomi dan Keuangan Syariah, 2025)
This study aims to analyse the profit-sharing system between owners and managers at Fourgee Mini Soccer and Bezzie Mini Soccer, and to assess its compliance with the provisions of the mudharabah contract under Islamic economic law. This study uses a normative empirical method, with both a legislative and a case approach. Normative data was obtained from Law Number 21 of 2008 concerning Islamic Banking, the Compilation of Sharia Economic Law, and the DSN-MUI Fatwa concerning Mudharabah, while empirical data was obtained through interviews with the owners and managers of both businesses. The results of the study show that the profit-sharing system at Fourgee Mini Soccer uses fixed nominal payments to managers, so that legally it is more accurately classified as an ijarah contract and does not meet the provisions of a mudharabah contract. Meanwhile, Bezzie Mini Soccer applies profit sharing based on a percentage, but this method is not supported by clear financial records and a written contract, so the applied mudharabah contract is not yet perfect (fasid). This study concludes that the profit-sharing systems in both businesses are not yet entirely consistent with the principles of mudharabah contracts as regulated under Islamic economic law and thus require improvements to the contract structure and recording mechanisms to achieve fair and transparent business cooperation.